Народы Севера и проблема управления Арктикой на конференции «Полярные чтения — 2019» - Терехин, А.Н.; Давыдов, В.Н. (ЖУРНАЛ СОЦИОЛОГИИ И СОЦИАЛЬНОЙ АНТРОПОЛОГИИ, 2019)
Acknowledgements. The review was prepared with the support of a grant from the Russian Science Foundation (project No. 18-18-00309).